1999
DOI: 10.1038/sj.bjp.0702795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia alone or combined with inflammation and 3‐methylcholanthrene on hepatic cytochrome P450 in conscious rabbits

Abstract: 1 To investigate the e ect of moderate hypoxia alone or combined with an in¯ammatory reaction or after 3-methylcholanthrene (3MC) pre-treatment on cytochrome P450 (P450), conscious rabbits were exposed for 24 h to a fractional concentration of inspired O 2 of 10% (mean PaO 2 of 34 mmHg). Hypoxia decreased theophylline metabolic clearance (Cl M ) from 1.73+0.43 to 1.48+0.13 ml min 71 kg 71 (P50.05), and reduced (P50.05) the formation clearance of theophylline metabolites, 3-methylxanthine (3MX), 1-methyluric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…In particular, obese individuals with systemic hypoxemia (because of sleep-related breathing disorders including obstructive sleep apnea) may experience repeated bouts of hepatic hypoxia, hepatocyte necrosis, and ultimately develop NASH. Several pieces of evidence support the possibility that hypoxemia may play a role in pathogenesis of NASH: First, sleep disturbances and nocturnal hypoxemia are common in patients with NASH (Table 2); second, hypoxemia has been shown to alter the activity of different CYPs 27,28 ; third, sleep apnea and hypoxemia have been associated with lipid peroxidation and oxidative stress 29 ; and, fourth, in the dietary model of animal NASH 6 as well as the human study by Weltman et al, 8 CYP2E1 activity was most prominent in zone III, the least oxygenated area of the acinus. The significant association noted in this study between hepatic CYP2E1 activity and nocturnal hypoxemia is interesting.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, obese individuals with systemic hypoxemia (because of sleep-related breathing disorders including obstructive sleep apnea) may experience repeated bouts of hepatic hypoxia, hepatocyte necrosis, and ultimately develop NASH. Several pieces of evidence support the possibility that hypoxemia may play a role in pathogenesis of NASH: First, sleep disturbances and nocturnal hypoxemia are common in patients with NASH (Table 2); second, hypoxemia has been shown to alter the activity of different CYPs 27,28 ; third, sleep apnea and hypoxemia have been associated with lipid peroxidation and oxidative stress 29 ; and, fourth, in the dietary model of animal NASH 6 as well as the human study by Weltman et al, 8 CYP2E1 activity was most prominent in zone III, the least oxygenated area of the acinus. The significant association noted in this study between hepatic CYP2E1 activity and nocturnal hypoxemia is interesting.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the serum of rabbits with acute inflammatory reaction down-regulate various CYP enzymes noncompetitively through several mediators [120]. In addition, it has been reported that acute moderate hypoxia and inflammation individually inhibited CYP; nevertheless, the combination of hypoxia and the inflammatory reaction restores CYP activity [110]. It was postulated that hypoxia can inhibit T-cell function which is necessary for the CYP down-regulation during inflammatory reaction [110].…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…In experimental animals and in humans, hypoxia alone or hypoxia and inflammation modulated CYP450 enzymes causing both a down-regulation of total hepatic CYP450 content and expression of some CYP450 isoenzymes as well as an up-regulation of other isoenzymes and their mRNA through the release of numerous cytokines such as IL-1␤, IL-2, IL-4, IL-5, TNF-␣, and IFN-␥, [151][152][153][154] and erythropoietin, 155,156 which can induce changes in the expression of CYP450 genes. 157,158 Hypoxia triggered also the expression and release of various inflammatory mediator receptor antagonists in a variety of cell types, eg, in mitogen-activated mononuclear cells, hypoxia enhanced IL-1 receptor antagonist (IL-1 Ra) mRNA expression and concomitantly increased, albeit to a lesser extent, both IL-1␣ and IL-1␤ mRNA expression and release in the surrounding environment.…”
Section: Abnormalities In the Central Nervous Systemmentioning
confidence: 99%